2005
DOI: 10.1002/pola.20980
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of redox cellulose Langmuir–Blodgett films containing a ferrocene derivative

Abstract: The 3-ferrocenoylpropanoyl group, one of the redox species, was introduced at C-2 and/or C-3 positions of 6-O-(4-stearyloxytrityl)cellulose. The spreading behavior of the cellulose derivatives on the water surface and the properties of Langmuir-Blodgett (LB) films were investigated. The surface pressure-area isotherm of the cellulose monolayer was changed by the subphase temperature. Uniform monolayers of 6-O-(4-stearyloxytrityl)cellulose 3-ferrocene propionate (STCFc) could be deposited successively onto seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…[11][12][13][14] In addition, the LB films of highly regioselectively substituted cellulose derivatives with a controlled pattern of functionalization and with well defined supramolecular nanoscale architecture, based on the basic concept of the role-sharing functionalization of cellulose, have bright prospects in the development of molecular assemblies with highly efficient photo-energy conversion. [15,16] We report herein the fabrication of LB films consisting (Figure 1). …”
Section: Communicationmentioning
confidence: 99%
“…[11][12][13][14] In addition, the LB films of highly regioselectively substituted cellulose derivatives with a controlled pattern of functionalization and with well defined supramolecular nanoscale architecture, based on the basic concept of the role-sharing functionalization of cellulose, have bright prospects in the development of molecular assemblies with highly efficient photo-energy conversion. [15,16] We report herein the fabrication of LB films consisting (Figure 1). …”
Section: Communicationmentioning
confidence: 99%
“…As a result, these are useful in a range of applications and studies such as sensors [50,51], electro-active Langmuir-Blodgett films [52] and free-standing redox-active films [53]. Conducting polymers containing ferrocene on main conjugation path of polymer backbone were also synthesized [54,55].…”
Section: Ferrocene Polymersmentioning
confidence: 99%
“…Furthermore, the LB films of high-regioselectively substituted cellulose derivatives with controlled pattern of functionalization, designed based on our fundamental concept of role-sharing functionalization of cellulose (Ifuku et al 2005), may have the potential for the molecular assembly with efficient photo-energy conversion. In this context, we have recently reported the fabrication of the LB films consisting of a regioselectively substituted cellulose derivative having both a porphyrin moiety and stearoyl groups at the C-6 and C-2, 3 positions, respectively, and indicated that the quantum yields of its LB films were higher than those of the conventional porphyrin LB films (Sakakibara et al 2007b).…”
Section: Introductionmentioning
confidence: 99%